2005
DOI: 10.1099/ijs.0.63353-0
|View full text |Cite
|
Sign up to set email alerts
|

Jiangella gansuensis gen. nov., sp. nov., a novel actinomycete from a desert soil in north-west China

Abstract: A novel actinomycete strain, designated YIM 002T, was isolated from a desert soil sample in Gansu Province, north-west China. This actinomycete isolate formed well-differentiated aerial and substrate mycelia. In the early stages of growth, the substrate mycelia fragmented into short or elongated rods. Chemotaxonomically, it contained ll-2,6-diaminopimelic acid in the cell wall. The cell-wall sugars contained ribose and glucose. Phospholipids present were phosphatidylinositol mannosides, phosphatidylinositol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
35
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…On the basis of the phenotypic and DNA-DNA hybridization data presented, strain D8-87 T is considered to represent a novel species of the genus Jiangella, for which the name Jiangella alkaliphila is proposed. The type strain is D8-87 T (5JBRI 2008 T 5KCTC 19222 T 5DSM 45079 T ).The genus Jiangella was proposed by Song et al (2005) to accommodate an actinomycete isolated from a desert soil in north-west China. At the time of writing, Jiangella gansuensis remains the type and only species of the genus.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of the phenotypic and DNA-DNA hybridization data presented, strain D8-87 T is considered to represent a novel species of the genus Jiangella, for which the name Jiangella alkaliphila is proposed. The type strain is D8-87 T (5JBRI 2008 T 5KCTC 19222 T 5DSM 45079 T ).The genus Jiangella was proposed by Song et al (2005) to accommodate an actinomycete isolated from a desert soil in north-west China. At the time of writing, Jiangella gansuensis remains the type and only species of the genus.…”
mentioning
confidence: 99%
“…Chemotaxonomically, the genus is characterized by the presence of LL-2,6-diaminopimelic acid (LL-DAP) in the cell-wall peptidoglycan, MK-9(H 4 ) as the major menaquinone, anteiso-C 15 : 0 , anteiso-C 17 : 0 , iso-C 15 : 0 , iso-C 16 : 0 and C 17 : 1 v8c as major fatty acids and a DNA G+C content of 70 mol%. 16S rRNA gene sequence analyses (Song et al, 2005) indicated that the genus belongs to the family Nocardioidaceae Nesterenko et al 1985 within the suborder Propionibacterineae.During the course of studies on the diversity of cave bacteria, a mycelium-forming actinomycete, designated strain D8-87 T , was isolated from the soil of a natural cave in Jeju, Republic of Korea, and its taxonomic status was investigated by a polyphasic approach. Strain D8-87 T was isolated by a dilution plating method on starch-casein agar as the selective medium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At present, this genus comprises only two species, Jiangella gansuensis (Song et al, 2005) and Jiangella alkaliphila (Lee, 2008), which were both isolated from soil samples. In this paper, we describe the polyphasic characterization of strain YIM 61503 T isolated from an endophytic environment.…”
mentioning
confidence: 99%
“…The genus Jiangella was proposed by Song et al (2005) to accommodate an aerobic, Gram-positive actinomycete with LL-2,6-diaminopimelic acid (LL-DAP) in the cell-wall peptidoglycan and MK-9(H 4 ) as the predominant menaquinone. At present, this genus comprises only two species, Jiangella gansuensis (Song et al, 2005) and Jiangella alkaliphila (Lee, 2008), which were both isolated from soil samples.…”
mentioning
confidence: 99%